PERAN KEPOLISAN POLRESTA BARELANG TERHADAP EKSPOLITASI ANAKDALAM MENGANGGULANGI TINDAK PIDANA ANAK DI WILAYAH KOTA BATAM - Pratama, Rizky; Jamba, Padrisan (LPPM Universitas Putera Batam, 2023)
Sexual exploitation is currently a profitable global business. This business is referred to as sex trafficking onan international scale. Women and children are forced into sex slavery by being sold, kidnapped, tortured, orraped whose main goal is to gain huge profits. Speaking in the context of decency, there are many thingsthat influence children to be easily exploited as sex workers, such as social media, the communityenvironment, and their own family environment. Social media is a tool where exploitation cases can occur. Inlaw enforcement (criminal) the police are the body that really determines the process of settling a criminalcase. This can be seen in the criminal justice system, where the police are the first agency to handle criminalcases. The authority given will result in a settlement or screening of violations of the law. From the results ofresearch carried out preventively in the form of prevention such as outreach to elements of society byworking with related agencies, then monitoring several public facilities in Batam City and in handling policecases from each region, especially the Barelang Police call for cooperation from various parties to preventand arrest suspects